Confidence And Practice Of Teaching Arabic In Specific Professional Standards/ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯Ø§Øª Ø§Ù„ØªØ¯Ø±ÙŠØ³ÙŠØ© ÙˆÙ…Ù…Ø§Ø±Ø³Ø§Øª Ù„Ù„ØªØ¯Ø±ÙŠØ³ ÙÙŠ Ø¶ÙˆØ¡ Ø§Ù„Ù…Ø¹Ø§ÙŠÙŠØ± Ø§Ù„Ù…Ù‡Ù†ÙŠØ© Ø§Ù„ØªØ®ØµØµÙŠØ© - AlBedayr, Jawaher (Ijaz Arabi Journal of Arabic Learning, 2021)
This study aimed to explore the teaching beliefs of Arabic teachers and their practice of teaching elementary pupils in the light of specialized professional standards in the context of virtual classes. To achieve the data, the researcher used semi-restricted interviews and structured observations with participants selected by the "target sample" strategy; To obtain an in-depth understanding of four female teachers' beliefs and teaching practices. The study results revealed that all female teachers have similar beliefs that are often contrary to specialized professional standards. The results also revealed some differences in the beliefs of female teachers, with interview data indicating that although female teachers have some beliefs about modern and appropriate strategies for teaching language skills to beginners, their practices were traditional. In the light of these findings, some recommendations were made.